Potencial de complexo nutricional à base de calcita e silício sobre a incidência de pragas e doenças na cultura do milho - Rombaldi, Rafael (2022)
Corn (Zea mays L.) is one of the main crops in the country and in the world. Thus, the objective of this work was to evaluate the potential of the calcite and silicone based nutritional complex on the phytosanitary parameters related to the corn crop. The work was carried out in the municipality of Saudade do Iguaçu, where Agroceres corn seeds, variety AG 9030, were used. Sowing took place in March 2021, with a spacing of 45 centimeters between rows. The experimental design was randomized blocks, with 10 replications, composed of plots of two cultivation lines of 50 meters in length. There were two treatments, the control with the phytosanitary management used by the producer, and the use of the calcite and silicon based product, at a dosage of 750 g/ha, in four applications, being: 1st VC; 2nd (14 days interval), 3rd in V8 and 4th in VT. The variables evaluated were the incidence of pests and diseases carried out from the first application at 20-day intervals, starting at 70 days (R1) until the end of the crop cycle (110 days - R6). The application of calcite and silicon was able to significantly reduce the incidence of diseases in corn, and this difference was observed at 70 days after emergence. The use of silicon did not affect the incidence of pests in corn under the conditions evaluated.